Stock ownership and political behavior: Evidence from demutualization - Markku Kaustia; Samuli Knüpfer; Sami Torstila (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
A setting in which customer-owned mutual companies converted to publicly listed firms created a plausibly exogenous shock to salience of stock ownership. We use this shock to identify the effect of stock ownership on political behavior. Using IV regressions, difference-in-differences analyses, and matching methods, we find the shock changed the way people vote in the affected areas, with the demutualizations being followed by a 1.7–2.7 percentage points increase in rightof- center vote share. Analyses of demutualizations that did not involve public listing of shares suggest that explanations based on wealth, liquidity, and tax-related incentives do not drive the results.
urn:nbn:de:hebis:30:3-293706
Keywords: D72; G11; P16; 330; Stock market participation; political behavior; salience; attention